2001
DOI: 10.1053/euhj.2000.2294
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac risk factors, medication, and recurrent clinical events after acute coronary disease. A prospective cohort study

Abstract: The present results indicate that the benefit of cardiac rehabilitation therapy following acute coronary events is only partially maintained during the following year. Continuous strategies of medical care need to be developed to improve the long-term outcome in coronary patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
3
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 21 publications
9
93
3
7
Order By: Relevance
“…A previous study revealed a 63.4% prevalence of hypertension among ACS patients [24]. However, in patients with acute myocardial infarction (AMI), the prevalence of hypertension varies from 31 to 59% [25]. A recent study from Barazil has reported that the main risk factors were arterial hypertension (68%), smoking (67%), and dyslipidemia (43%) [26].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed a 63.4% prevalence of hypertension among ACS patients [24]. However, in patients with acute myocardial infarction (AMI), the prevalence of hypertension varies from 31 to 59% [25]. A recent study from Barazil has reported that the main risk factors were arterial hypertension (68%), smoking (67%), and dyslipidemia (43%) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Este fator pode se mostrar importante, uma vez que absenteísmos em cuidados contínuos de saúde em coronariopatas é algo ainda considerado problemático. [20][21][22] Por conta disto, acredita-se que desenvolver as habilidades auto reguladoras, nessa população, implica em alta aderência à comportamentos saudáveis e ao exercício físico. Adicionalmente, a aderência a programas de RCPM tem sido influenciada por barreiras relatadas pelos pacientes.…”
Section: Discussão E Considerações Finaisunclassified
“…meet the recommendations. 7,8 There is very little evidence on PA behavior over the long term (2 or more years).…”
Section: Introductionmentioning
confidence: 99%
“…meet the recommendations. 7,8 There is very little evidence on PA behavior over the long term (2 or more years).Encouraging positive health behaviors among CR graduates is a complex process that involves many levels of influence. To examine these levels of influence, a comprehensive approach to health promotion must be employed, such as the socioecological model.…”
mentioning
confidence: 99%